Activity of paraoxonase 1 and lipid profile in healthy children - Sumegová, Katarína; Nagyová, Zuzana; Waczulíková, Iveta; Žitňanová, Ingrid; Ďuračková, Zdeňka (Physiological research, 2007)
Paraoxonase 1 (PON1) seems to have a relevant role in detoxifying processes and in atherosclerosis. The aim of this study was to determine PON1 activity, the total antioxidant capacity, as well as entire lipid profile in children for screening of possible risk of atherosclerosis development. Serum PON1 arylesterase/paraoxonase activities were determined spectrophotometrically. The total antioxidant capacity of the serum was measured by TEAC method. Parameters of lipid profile were analyzed by routine laboratory methods. It has been shown that PON1 arylesterase/ paraoxonase activities were very similar to values found in adults. In children, no significant correlation between PON1 arylesterase activity and HDL was observed. PON1 paraoxonase activity correlated only with atherogenic index. PON1 arylesterase activity was significantly higher in girls than in boys. The antioxidant capacity was inversely related to the body mass index. In this study, PON1 activity was determined in healthy children aged 11 to 12 years and we found a similarity in PON1 activities of children and adults. Moreover, the results of our study support the hypothesis that higher body weight of children may contribute to a greater risk for development of atherosclerosis in which oxidative stress plays a role.
Keywords: finanční podpora výzkumu jako téma; lipidové peroxidy; Antioxidants; dítě; lidé; lipoproteiny HDL; Lipid Peroxides; Risk Factors; tělesná hmotnost; Atherosclerosis; Aryldialkylphosphatase; Data Interpretation, Statistical; Research Support as Topic; aryldialkylfosfatasa; interpretace statistických dat; antioxidancia; rizikové faktory; Body Weight; ateroskleróza; Child; Lipoproteins, HDL; Humans